1997
DOI: 10.1590/s0100-879x1997000700012
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the isolated perfused rat tail vascular bed

Abstract: Isolated segments of the perfused rat tail artery display a high basal tone when compared to other isolated arteries such as the mesenteric and are suitable for the assay of vasopressor agents. However, the perfusion of this artery in the entire tail has not yet been used for functional studies. The main purpose of the present study was to identify some aspects of the vascular reactivity of the rat tail vascular bed and validate this method to measure vascular reactivity. The tail severed from the body was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Isolated rat tail arteries were perfused as previously reported (22). Rats were first anesthetized with sodium pentobarbital (65 mg/kg, ip), and heparin (500 IU, ip) was administered 10 min later.…”
Section: Isolated Rat Tail Vascular Bed Preparationmentioning
confidence: 99%
“…Isolated rat tail arteries were perfused as previously reported (22). Rats were first anesthetized with sodium pentobarbital (65 mg/kg, ip), and heparin (500 IU, ip) was administered 10 min later.…”
Section: Isolated Rat Tail Vascular Bed Preparationmentioning
confidence: 99%
“…Isolated tail vascular bed preparations were obtained from rats 4 weeks after MI and anesthetized with sodium pentobarbital (60 mg/kg i.p. ), as previously described (França et al, 1997). Briefly, after anesthesia, the tail artery was cannulated, and the tail was immediately severed from the body.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Isolated rat tail vascular beds were used in this study as previously reported (10). Briefly, the rats were anesthetized with sodium pentobarbital (65 mg/kg, ip) and heparin (500 IU, ip) was administered after loss of the righting reflex.…”
Section: Anesthetized Animalsmentioning
confidence: 99%